Noninvasive assessment of liver fibrosis with the aspartate transaminase to platelet ratio index (APRI): Usefulness in patients with chronic liver disease - (:unkn) unknown (BAQIYATALLAH RESEARCH CENTER, 2011)
Background: The aspartate aminotransferases (AST) to platelet ratio index (APRI) may serve as a noninvasive marker to assess liver fibrosis. Objectives: To assess the diagnostic ability of the APRI for prediction of fibrosis in patients with chronic hepatitis B (CHB), chronic hepatitis C (CHC), and non-alcoholic fatty liver disease (NAFLD). Patients and Methods: This retrospective study included 207 patients with CHB,108 with CHC, and 140 patients with NAFLD. The APRI was calculated as (AST level/upper normal limit for AST)/platelet counts (109/L) x 100. The stage of liver fibrosis in patients with chronic viral hepatitis was graded using the METAVIR scale. The Kleiner system for grading fibrosis was used in patients with NAFLD. Results: Bivariate correlation analyses showed that the APRI was significantly associated with fibrosis scores in patients with CHC (p = 0.2634, p = 0.0059) and NAFLD (p = 0.2273, p = 0.0069), but not in those with CHB (p = 0.1005, p = 0.1495). Receiver operating characteristic (ROC) curves were used for assessing the ability of the APRI as a predictor of the absence or presence of liver fibrosis (fibrosis score of 0 vs fibrosis scores of 1-4). In patients with CHC, the APRI showed a sensitivity of 72.7% and a specificity of 62.4% for detection of fibrosis (p<0.01). In the NAFLD group, the APRI showed a sensitivity of 60.0% and specificity of 73.3% for detection of fibrosis (p<0.01). In patients with CHB, the APRI showed a sensitivity of 55.0% and a specificity of 75.4% for fibrosis (p=NS). Conclusions: The APRI shows an acceptable accuracy for the assessment of liver fibrosis in patients with CHC and NAFLD, but not in those with CHB. (c) 2011 Kowsar M.P.Co. All rights reserved.
Keywords: Chronic hepatitis C; Chronic hepatitis B; Fatty liver; Fibrosis; Aspartate aminotransferases; CHRONIC HEPATITIS-C; BLOOD-TESTS; PREDICT; CIRRHOSIS; BIOPSY; FIBROSCAN(R); COINFECTION; VALIDATION; INFECTION; DIAGNOSIS